Comparing Dorsal Tangential and Lateral Views of the Wrist for Detecting Dorsal Screw Penetration after Volar Plating of Distal Radius Fractures - Juan M. Giugale; Mitchell S. Fourman; Deidre L. Bielicka; John R. Fowler (Advances in Orthopedics)
Background. The dorsal tangential (DT) view has been shown to improve the detection of dorsal screw perforation during volar distal radius fracture fixation. Here we performed a cadaveric imaging survey study to evaluate if the DT view was uniformly beneficial for all screws. Methods. Standardized placement of fixed-angle volar distal radius plates was performed on two cadavers. Fluoroscopic images depicting variable screw perforation of each of the four screw holes on the plate were generated. A 46-image survey was distributed at a large academic medical center. Respondents were asked to answer if the screw was perforating through the dorsal cortex in each image. Statistical analysis was performed using Fisher’s exact test. A p value < .05 was considered significant. Results. The DT view offered a significantly more reliable determination of dorsal screw penetration than traditional lateral imaging for the radial-most screw at all degrees of perforation and the middle two screws at 2 mm of perforation. Residents and attendings had more accurate screw readings overall using the DT view. Conclusions. The DT view is superior to traditional lateral imaging in the detection of small amounts of dorsal perforation of the radial-most three screws of a fixed-angle volar plate.